Predictive factors for premature birth and respiratory exacerbation in pregnancies of women with cystic fibrosis - Vanessa de Souza Vieira; Taiane dos Santos Feiten; Renata Salatti Ferrari; Paulo de Tarso Roth Dalcin; Bruna Ziegler (Elsevier, 2022)
Objective: In this present study, the authors evaluated the predictive factors for adverse maternal-fetal outcomes in pregnancies of women with cystic fibrosis (CF). Patients were followed up by a referral center for adults in southern Brazil. Methods: This is a retrospective cohort study that used data from electronic medical records regarding pregnancies of women diagnosed with CF. Results: The study included 39 pregnancies related to 20 different women. The main adverse outcomes were high prevalence rates of premature birth (38.5%) and maternal respiratory exacerbation (84.6%). Lower body mass index (BMI) values (< 20.8) and younger ages of CF diagnosis increased the risk of premature birth. The presence of methicillin-resistant and absence of methicillin-sensitive Staphylococcus aureus, as well as a younger age of diagnosis, increased the risk of maternal respiratory exacerbation during pregnancy. Conclusions: Conception in women with CF is often associated with maternal and fetal complications. Continuous monitoring by a multidisciplinary team should emphasize appropriate nutritional status, investigation of bacterial colonization, and immediate attention to respiratory exacerbations.